2022
DOI: 10.1038/s41467-022-31769-4
|View full text |Cite
|
Sign up to set email alerts
|

Integration of tumor extrinsic and intrinsic features associates with immunotherapy response in non-small cell lung cancer

Abstract: The efficacy of immune checkpoint blockade (ICB) varies greatly among metastatic non-small cell lung cancer (NSCLC) patients. Loss of heterozygosity at the HLA-I locus (HLA-LOH) has been identified as an important immune escape mechanism. However, despite HLA-I disruptions in their tumor, many patients have durable ICB responses. Here we seek to identify HLA-I-independent features associated with ICB response in NSCLC. We use single-cell profiling to identify tumor-infiltrating, clonally expanded CD4+ T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…We previously reported that the degree of induction of the IFNγ Hallmark response as well as a T cell signature [49] in on-treatment biopsies associate with the duration of therapeutic benefit in patients bearing EGFR mutant lung cancers [18]. Herein, we demonstrate that the magnitude of two additional gene expression signatures previously shown to predict responsiveness to anti-PD-1-based immune therapy [42, 43] also associate with longer time to progression on EGFR TKIs ( Figure 1 ). Thus, there is ample evidence for immune engagement by human EGFR mutant lung cancers despite their lack of sensitivity to anti-PD-1 therapies [44-46], a feature that is shared by orthotopic tumors derived from the murine EGFR mutant cell lines (data not shown).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…We previously reported that the degree of induction of the IFNγ Hallmark response as well as a T cell signature [49] in on-treatment biopsies associate with the duration of therapeutic benefit in patients bearing EGFR mutant lung cancers [18]. Herein, we demonstrate that the magnitude of two additional gene expression signatures previously shown to predict responsiveness to anti-PD-1-based immune therapy [42, 43] also associate with longer time to progression on EGFR TKIs ( Figure 1 ). Thus, there is ample evidence for immune engagement by human EGFR mutant lung cancers despite their lack of sensitivity to anti-PD-1 therapies [44-46], a feature that is shared by orthotopic tumors derived from the murine EGFR mutant cell lines (data not shown).…”
Section: Discussionmentioning
confidence: 68%
“…Using previously reported RNAseq data from pre- and on-treatment biopsies collected from EGFR mutant LUAD patients, the sums of the 18 genes in the signature described by (A) Ayers et al [42] and the 25 genes in the signature described by (B) Lau et al [43] were calculated for each patient-derived specimen and converted to Z-scores. The resulting values for the Ayers ( A ) and Lau et al ( B ) signatures were binned by TTP of less than or greater than 12 months where the eight patients exhibited TTP of 6, 6.2, 8.3, 8.6 12.5, 13, 13.1 and 16.3 months (mean and median = 10.5 and 10.6 months, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lau et al [ 63 ] demonstrated that NSCLC tumor cells expressed human leucocyte antigen (HLA)-II transcripts, mainly HLA-DRB1. Besides, they identified a cluster of cytotoxic GZMB CD4 + T cells that expressed high levels of PDCD1 and CTLA4, suggesting that this population could be involved in the anti-tumor response after immunotherapy.…”
Section: Relevance Of Single-cell Technologies In the Identification ...mentioning
confidence: 99%